Expanding the students' vocabulary by using musical flashcards at kindergarten school - Salma Hira; Siti Ngaisah; Ekka Zahra Puspita Dewi; Febry Wulandari; Nabila Fateha; Ana Safitri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2025)
Kindergarten learners frequently faced challenges in retaining vocabulary due to repetitive learning tasks, necessitating prompt measures to enhance classroom techniques. This research wanted to boost vocabulary proficiency among kindergarten students by utilizing